2010
DOI: 10.1002/nvsm.407
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the social impact of charitable organizations—four alternative approaches

Abstract: There is increased societal pressure on charities to improve performance. The questions that they must ask are: (1) Who is our audience? (2) What evaluation measures are important to the organization? and (3) What evaluation measures are best for the organization? There are a number of different approaches available for assessing performance, ranging from social accounting to more informal qualitative assessments of whether the organization's mission is being achieved. This paper draws on the industry and acad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 43 publications
(51 reference statements)
1
21
0
Order By: Relevance
“…Measurement standards should refer not only to attributes of measured objects, but also to guidelines concerning individual dispositions during the measurement process (i.e. Given the multifaceted nature of social value and the necessity to engage multiple stakeholders in the SVM process, authors have concluded that successful implementations require a host of approaches (Costa and Pesci 2016;Hall et al 2015;Polonsky and Grau 2011). Potential theoretical lens: institutional theory.…”
Section: Focus Of Svmi Research Svm Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Measurement standards should refer not only to attributes of measured objects, but also to guidelines concerning individual dispositions during the measurement process (i.e. Given the multifaceted nature of social value and the necessity to engage multiple stakeholders in the SVM process, authors have concluded that successful implementations require a host of approaches (Costa and Pesci 2016;Hall et al 2015;Polonsky and Grau 2011). Potential theoretical lens: institutional theory.…”
Section: Focus Of Svmi Research Svm Toolsmentioning
confidence: 99%
“…Measurement design and implementation should focus not only on tools, processes and results, but also on how subjects interact with the measurement process. Potential theoretical lens: phenomenology Stated purposes SVM is the process of describing, monitoring, and communicating the effects in users' or communities' conditions of an organizational activity, process or service (Benjamin 2013;Boyne and Law 2005;Esteves et al 2012;Kroeger and Weber 2014;Nguyen et al 2015;Plantz et al 1997;Polonsky and Grau 2011;Vanclay 2002). SVM is used for accountability to, and engagement of, stakeholders (e.g.…”
Section: Focus Of Svmi Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The contested nature of social impact affects the different approaches of its evaluation (Arvidson et al, 2013;Dey and Gibbon, 2017;Polonsky et al, 2016;Polonsky and Grau, 2011). Scholars have debated several methods to explore the contribution of nonprofit organizations in responding to needs in the nonprofit management literature, the social entrepreneurship literature and the programme evaluation literature (Bagnoli & Megali, 2009;Epstein & Klerman, 2012;Leeuw & Vaessen, 2009;Kroeger & Weber, 2014;Grieco et al, 2015).…”
Section: Social Impact Methodsmentioning
confidence: 99%
“…Interested readers can found in depth literature from Sargeant and Woodliffe (2007b) or more recently from Bekkers and Wiepking (2011) for comprehensive review of charitable donation. From the nonprofit management perspective, better communication and multiple engagements have been hypothesized as antecedents of donor active commitment (Sargeant and Woodliffe 2005;Bennett 2013;Webber 2004;Polonsky and Grau 2011). Public support from government grants and foundation giving tend to be more concerned of accountability, performance, and social values, which could be defined from four perspectives, i.e., Operating Efficiency; Achievement of Organizational Objectives; Return on Investment; Social Outcomes (Polonsky and Grau 2008), and performance measures and reporting are being promoted and standardized for practicality and utility (Urban Institute 2006).…”
mentioning
confidence: 99%